2012
DOI: 10.1149/2.058204jes
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Speciation of Lanthanum 4-Hydroxy Cinnamate and its Impact on the Corrosion Inhibition Mechanism for AS1020 Steel

Abstract: Speciation of the inhibitor lanthanum 4-hydroxy cinnamate in solution as a function of pH and concentration has been evaluated and correlated with corrosion inhibition efficiency for AS1020 steel in an aqueous chloride solution. A combination of nuclear magnetic resonance (NMR) spectroscopy, electrospray mass spectrometry (ESMS), potentiodynamic polarization, scanning electron microscopy (SEM) and profilometric techniques were found to be useful in the characterization of this system. Potentiodynamic polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…In addition, a thinner surface film deposits on the entire steel substrate, as suggested by the EIS, XPS and SEM experiments, would account for a reduction in the cathodic kinetics (in contrast to the predominantly anodic inhibition seen in naturally-aerated systems and the addition of REM(4OHCin) 3 led to the formation of a continuous protective film on the steel surface). 26 The influence of inhibitor concentration is also consistent with this suggested mechanism, as the electrochemical results indicated improved performance, likely arising from better surface coverage with increasing amount of inhibitor. Pr(4OHCin) 3 appears to be the most efficient inhibitor under these conditions, showing the highest inhibition performance.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In addition, a thinner surface film deposits on the entire steel substrate, as suggested by the EIS, XPS and SEM experiments, would account for a reduction in the cathodic kinetics (in contrast to the predominantly anodic inhibition seen in naturally-aerated systems and the addition of REM(4OHCin) 3 led to the formation of a continuous protective film on the steel surface). 26 The influence of inhibitor concentration is also consistent with this suggested mechanism, as the electrochemical results indicated improved performance, likely arising from better surface coverage with increasing amount of inhibitor. Pr(4OHCin) 3 appears to be the most efficient inhibitor under these conditions, showing the highest inhibition performance.…”
Section: Resultssupporting
confidence: 61%
“…[25][26][27][28][29] One approach is to synthesize rare earth metal (REM) compounds with synergistic combinations of organic inhibitor molecules (rare earth organics). [25][26][27][28][29][30][31][32] It has been shown that by combining a rare earth metal with an organic ligand (such as a carboxylate) to create a multifunctional inhibitor that combines the inhibitive properties of the two components, with inhibition capability superior to that of either of the individual components at the same concentration is often observed. 25 Blin et al 25 showed some years ago that substituted rare earth organics, in particular lanthanum 4-hydroxycinnamate (La(4OHCin) 3 ), led to an enhancement in corrosion mitigation in oxygen-containing solutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pourbaix diagrams are often used as a guide for the types of deposit that might provide cathodic inhibition [128]. The deposit is usually a hydroxy-oxide, with rare earths currently of great interest [129][130][131][132][133][134][135][136][137][138]. Transition metal phosphates have traditionally been of great importance as well [139][140][141][142][143][144].…”
Section: Inhibitor Requirementsmentioning
confidence: 99%
“…These compounds can suppress both the anodic and cathodic reactions that are involved in corrosion, showing a synergistic effect between the rare earth metal and the carboxylates. [6][7][8] Among these, rare earth metal aromatic carboxylates have demonstrated the best anticorrosive performance due to the formation of a passive barrier layer that forms due to adsorption and subsequent reaction with the underlying alloy substrate. 7,9,10 From this past work, it is evident that the aromatic carboxylate, p-coumarate, provides very efficient inhibition.…”
mentioning
confidence: 99%